Case Report: Miles Surgery Ameliorates High Blood Pressure in a Rectal Carcinoma Patient With Essential Hypertension - Zhang, Meng-Wan; Fan, Bo-Shi; Yu, Jian-Guang (Frontiers in Cardiovascular Medicine, 2021)
Hypertension is one of the major causes of public health problems. Multiple factors affecting gastrointestinal tract function are involved in hypertension. Emerging studies have manifested that gut intervention may play significant roles in regulating blood pressure but the underlying mechanisms are complex and not fully clear. Here, we report a case report of sixty-six years old male who had a long history of hypertension and received Miles surgery for rectal carcinoma. The blood pressure of this patient was returned to normal levels after the operation. The possible reasons could be the modulation of sympathetic tone and the gut microbiota-brain axis. This report provides evidence about the relevance between hypertension and gut intervention particularly in the colorectal sites and gives hints for investigating the possible mechanisms of hypertension and the novel strategy for blood pressure control.